Analisis produktivitas untuk mengevaluasi losses tertinggi pada mesin filling produksi kosmetik - Panjaitan, Nadya Jessica; Dewi, Ratna Mustika; Kristiyani, Ika Murti (Universitas Atma Jaya Yogyakarta, 2025)
The productivity of filling machines is a critical factor in the skincare industry, but it is often hampered by various losses that have not been comprehensively measured. This research aims to identify the dominant types of losses affecting the efficiency of filling machines at PT XYZ through a qualitative approach. Based on the analysis, it turns out that at PT XYZ, there are 3 products with the highest loss percentages, namely A Body Wash, C Shampoo, and A Hand Wash. Among these products, A Body Wash has the lowest productivity achievement, with 20% of the products reaching a productivity rate of below 1%. The productivity of filling machines for skincare companies needs to show a tendency for low productivity values for Body Wash products.